2019
DOI: 10.1111/fwb.13250
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls on benthic food web functions and carbon resource use in subarctic lakes

Abstract: Climate warming and consequent greening of subarctic landscapes increase the availability of organic carbon to the detrital food webs in aquatic ecosystems. This may cause important shifts in ecosystem functioning through the functional feeding patterns of benthic organisms that rely differently on climatically altered carbon resources. Twenty‐five subarctic lakes in Finnish Lapland across a tree line ecotone were analysed for limnological and optical variables, carbon (δ13C) and nitrogen (δ15N) stable isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 90 publications
(167 reference statements)
3
19
0
Order By: Relevance
“…In addition to taxonomic compositions, applications of functional characteristics of aquatic organisms can be valuable for understanding ecosystem processes and dynamics (Jeppesen et al 2001;Nevalainen and Luoto 2017;Kivilä et al 2019). In Revvatnet, the changes in diatom ecological guilds support the environmental evidence derived from taxonomic compositions.…”
Section: Ecological Shiftsmentioning
confidence: 90%
“…In addition to taxonomic compositions, applications of functional characteristics of aquatic organisms can be valuable for understanding ecosystem processes and dynamics (Jeppesen et al 2001;Nevalainen and Luoto 2017;Kivilä et al 2019). In Revvatnet, the changes in diatom ecological guilds support the environmental evidence derived from taxonomic compositions.…”
Section: Ecological Shiftsmentioning
confidence: 90%
“…Based on the SI measurements from the chironomid remains, a three-source Bayesian mixing model was built with simmr (Parnell & Inger, 2016) in R (R Core Team, 2018) to examine the relative proportions of different nutritional sources incorporated into the chironomid assemblage. The model with the same attributes has been previously applied on a surface sediment data set by Kivilä et al (2019). The endmembers were based on published measurements from close-by region or similar environments (for further details see Kivilä et al, 2019, Appendix 2).…”
Section: Methodsmentioning
confidence: 99%
“…For secondary producers, habitat attributes (such as oxygen levels, substrate organic matter quantity and quality) and physiological factors (body size, developmental stage) have been noted important in defining the feeding mode and resource utilization (Merritt et al, 2008;Craig et al, 2015). In addition, Kivilä et al (2019) recently showed that occurrence of chironomid functional feeding groups (FFGs) was connected to habitat-related factors, such as DOC and nutrient concentrations. In this study, we use FFGs, which are defined by feeding mode but also have their general preferred type of nutrition (Mandaville, 2002;Merritt et al, 2008), to capture temporal patterns in functional assemblage composition and feeding modes, and assess their connections to environmental changes and macrobenthic resource utilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDA was performed with Canoco 5 software [33] and linear regressions with PAST3 software [34]. In addition to OM%, organic matter δ 13 C, and SSN, mean carbon source contributions in the benthic food web (based on fossil Chironomidae δ 13 C), modeled with a three-source (benthic, planktonic, and terrestrial) Bayesian mixing model previously applied in [22], were utilized as paleoenvironmental reference data. Here, the modeled planktonic and benthic carbon contributions (to Chironomidae diet) were used in a planktonic to benthic (P/B) ratio.…”
Section: Introductionmentioning
confidence: 99%